Social Trust, Trust Differential, and Radius of Trust on Volunteering: Evidence from the Hong Kong Chinese. Issue 47 (4th March 2021) - Liu, Susu; Wen, Zhuoyi; Su, Jionglong; Ming-lin Chong, Alice; Kong, Shiyi; Jiang, Zhengyong
Abstract: The promotion and development of sustainable volunteerism is crucial for quality social services. Previous studies on the relationship between social trust and volunteering is mixed and inclusive. This article aims to investigate the effects of the particularized trust, generalized trust, trust differential (i.e., difference in levels between particularized and generalized trust) and radius of trust (i.e., difference in levels between in-group trust and out-group trust), on volunteering. By interviewing 1, 170 Hong Kong Chinese in a territory-wide randomized household survey, this article reveals that generalized trust facilitates volunteering, whereas particularized trust exhibits an inverse effect. The radius of trust could not facilitate voluntary participation. This article distinguishes between the reverse contributions of generalized and particularized trust among Hong Kong Chinese, thereby providing a clear and precise explanation for social trust-volunteering relationships. Future research should focus on the conceptualization and operationalization of radius of trust and cross-cultural comparative studies on the effects of particularized and generalized trust using longitudinal data.